2011
DOI: 10.1007/s11368-011-0399-3
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus transfer across boundaries: from basin soils to river bed sediments

Abstract: Purpose The study of phosphorus (P) transfer from soils to rivers is a subject of interest as there is a clear relation between land use and water quality. P transfer in the soil/sediment system was evaluated by comparing the concentrations of total (P T ) and bioavailable P (P A ). Materials and methods Phosphorus concentrations were measured in three different compartments following the natural transport route in a basin: soils, suspended and riverbed sediments. Soils were sampled from five different types o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Because the nutrients and sediments transported from watersheds depend strongly on rate of loading and of sediment erosion into rivers (Lukkari et al, 2008;Pacini and Gächter, 1999) and on watershed characteristics such as hydrology, geology, soils, topography, and land use (Iglesias et al, 2011;Jiang et al, 2010Jiang et al, , 2012Woli et al, 2004), they are expected to vary in space and in time in a lake. Jin et al (2006) reported spatial variation in different P fractions in sediments and a relationship between these variations and the trophic status of different parts of Taihu Lake.…”
Section: Introductionmentioning
confidence: 99%
“…Because the nutrients and sediments transported from watersheds depend strongly on rate of loading and of sediment erosion into rivers (Lukkari et al, 2008;Pacini and Gächter, 1999) and on watershed characteristics such as hydrology, geology, soils, topography, and land use (Iglesias et al, 2011;Jiang et al, 2010Jiang et al, , 2012Woli et al, 2004), they are expected to vary in space and in time in a lake. Jin et al (2006) reported spatial variation in different P fractions in sediments and a relationship between these variations and the trophic status of different parts of Taihu Lake.…”
Section: Introductionmentioning
confidence: 99%
“…Arsenic release is also promoted in high ionic strength conditions, as it is characteristic of estuarine environments where the mixture of fresh and marine waters occurs [73]. The release of arsenic is favored by the presence of phosphate, showing high concentrations in some sections of the river [194][195][196], coming from wastewaters discharged into the river course and fertilizers eroded or leached from the soils of the basin. Interestingly, although phosphate favors arsenic release from the Anllóns sediments, it was shown in Microtox ® bioassays that it counteracts the acute toxicity of arsenate, but has no effect on the toxicity of arsenite and DMA V [197].…”
Section: The Anllóns River: Polluted Sediments Resulting From Former mentioning
confidence: 99%
“…Previous studies revealed that fine particles are selectively eroded from the soil surface and easily transported downstream and exhibit preferential export of nonapatite P (NaOH 25 -P, BD-P, and NaOH 85 -P), resulting in higher proportions of labile or bioavailable forms of inorganic-P in lakes or rivers related to the basin soils. 30,31 This could partially explain the spatial patterns of sediment P fractionation in the river networks across the Lake Taihu basin, where the fraction of HCl-P was predominant in the upstream. In the upstream areas of agriculture, soil erosion could also be important to the load of coarse particles with a short transport pathway or due to bank failure, 31,32 resulting in a higher proportion of HCl-P from nonpoint sources.…”
Section: ■ Discussionmentioning
confidence: 99%